THE INFLUENCE OF STRATEGIC MANAGEMENT ON ACHIEVING SALES TARGET AT PT WOM FINANCE MADIUN - Irma Nisa'ul Safitri; Nur Hidayah; Ayi Hendriawan (International Journal of Economics, Science, and Education, 2024)
This study aims to analyze how strategic management influences sales target achievement at PT WOM Finance. The data studied are in the form of questionnaire results on how much influence strategic management has on target achievement at PT WOM Finance. In this study, the researcher used a quantitative method. The data source comes from the population and samples, namely employees of PT WOM Finance. Data collection techniques use observation, interviews, and questionnaires. The data analysis technique for this study uses simple linear regression. The results of this study are based on the results of data analysis and inferential statistics for hypothesis testing . The results of the validity test state that six items from variable X are declared valid and one item is declared invalid, then in variable Y all items are declared valid. While from the reliability test all variables are declared reliable. Based on this study, it states that the influence between the implementation of strategic management on the achievement of financing product sales targets on variable X against Y is positive, giving a significant influence, which means that the variable has a role in achieving financing product sales targets. The implementation of strategic management in product management is very necessary to support the success or achievement of better product sales targets, which are in accordance with expectations.